THE NECESSITY OF ECOLABELING IN NATIONAL DAIRY PRODUCTION - O. Kharina (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article highlights the main trends in dairy enterprises in Ukraine, considered a set of problems of institutional nature, and the problem of low quality of domestic dairy products revealed the factors that affect it. The necessity of a complete certification of enterprises of domestic milk processing sector and the introduction of eco-labels for manufactured dairy products was improved. The author analyses the main advantage of consumers and producers of dairy products from the introduction of ecological labeling. It is established that dairy enterprise urgent need to improve the system of environmental and economic management at all it levels.